9
$\begingroup$

We can prove that $$\sum_{n=2}^{\infty}\frac{(-1)^n}{n}\zeta(n)=\gamma$$

In fact, If we let $f(z)=\sum_{m=2}^\infty\frac{(-1)^m}m z^m$, then by the method which used in this question,

$$\sum_{n=2}^{\infty}\frac{(-1)^n}{n}\zeta(n)=\sum_{n=1}^nf\left(\frac1 n\right)=\sum_{n=1}^\infty\sum_{m=2}^\infty\frac{(-1)^m}{mn^m}=\sum_{n=1}^\infty\left(\frac1 n+\log\left(1-\frac1 n\right)\right)=\gamma$$

Is there any known value for $\displaystyle \sum_{n=2}^{\infty}\frac{(-1)^n}{n^k}\zeta(n)$ for every natural number $k\ge2$? What is the best result?

$\endgroup$

migrated from mathoverflow.net Oct 19 '13 at 13:25

This question came from our site for professional mathematicians.

5
+200
$\begingroup$

I don't know if this can help, probably not, but from $$\sum_{n=2}^{\infty}\frac{\left(-1\right)^{n}x^{n}}{n}\zeta\left(n\right)=x\gamma+\log\left(\Gamma\left(x+1\right)\right)$$ we can get $$\sum_{n=2}^{\infty}\frac{\left(-1\right)^{n}x^{n-1}}{n}\zeta\left(n\right)=\gamma+\frac{\log\left(\Gamma\left(x+1\right)\right)}{x}$$ and so $$\sum_{n=2}^{\infty}\frac{\left(-1\right)^{n}x^{n}}{n^{2}}\zeta\left(n\right)=\gamma x+\int_{0}^{x}\frac{\log\left(\Gamma\left(y+1\right)\right)}{y}dy$$ note that for $x=1$ we have the GEdgar's result. With the same method, we can get $$\sum_{n=2}^{\infty}\frac{\left(-1\right)^{n}x^{n}}{n^{3}}\zeta\left(n\right)=\gamma x+\int_{0}^{x}\frac{1}{t}\left(\int_{0}^{t}\frac{\log\left(\Gamma\left(y+1\right)\right)}{y}dy\right)dt$$ and so on. Surely these integrals are quite frightful.

$\endgroup$
  • 3
    $\begingroup$ It seems that there is no a nice closed form yet! $\endgroup$ – user91500 Oct 12 '15 at 9:19
7
$\begingroup$

I only get $$ \sum _{n=2}^{\infty }{\frac { \left( -1 \right) ^{n}\zeta \left( n \right) }{{n}^{2}}} = \gamma+\int _{0}^{1}\!{\frac {\ln \left( \Gamma \left( s+1 \right) \right) }{s}}{ds} $$ Probably not much help.

$\endgroup$
  • $\begingroup$ How did you get that? $\endgroup$ – draks ... Sep 22 '15 at 10:25
  • $\begingroup$ @draks... take the logarithm of Weierstrass' form of the Gamma function to obtain $\sum_{n=2}^{\infty}\frac{(-1)^n\zeta(n)}{n}x^n=\gamma x+\log\Gamma(x+1)$ $\endgroup$ – nospoon Sep 22 '15 at 11:00
  • $\begingroup$ @nospoon is there a square missing ? $\endgroup$ – draks ... Sep 22 '15 at 11:23
  • $\begingroup$ @draks... No. divide the above equation by $x$ and integrate from $0$ to $1$. $\endgroup$ – nospoon Sep 22 '15 at 11:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.